2020
DOI: 10.2188/jea.je20190165
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations of Toothbrushing With Obesity and Hyperglycemia

Abstract: Background: Toothbrushing is a health-related lifestyle habit and has been reported to contribute not only to oral health but also to some parameters of general health; however, little research has been conducted to understand the association of the frequency and timing of toothbrushing with the development of comprehensive metabolic abnormalities, with consideration of oral health condition. In this study, using longitudinal data, we examined this association in Japanese adults, adjusting for periodontal cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…In this study, we demonstrated that less frequent toothbrushing was associated with higher risk DM, which is in line with previous ndings 14, [23][24][25] . A recent meta-analysis including 20 studies showed that a lower frequency of toothbrushing was associated an increased risk of DM (OR:1.32, 95% CI:1.19-1.47) 23 .…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we demonstrated that less frequent toothbrushing was associated with higher risk DM, which is in line with previous ndings 14, [23][24][25] . A recent meta-analysis including 20 studies showed that a lower frequency of toothbrushing was associated an increased risk of DM (OR:1.32, 95% CI:1.19-1.47) 23 .…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with the previously conducted research [ 22 ]. Similarly, research conducted in Japan, identified positive association between obesity and lower frequency of brushing habits [ 34 ]. Similarly, research by Park et al also identified positive association between obesity and time of brushing teeth and use of mouthwash [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous cross-sectional study, less-frequent tooth brushing was associated obesity, even after adjusting for oral health indicators (odds ratio: 1.22 and 1.48 for tooth brushing frequency of 1 time/day and 0 time/day, respectively) [ 22 ]. In addition, a recent general population-based longitudinal study of 4537 participants in Japan demonstrated that a low frequency of tooth brushing (≤1 time/day) was associated with the occurrence of obesity (prevalence rate ratio: 1.77, 95% confidence interval: 1.12–2.80) [ 23 ]. Our research results were similar to these previous studies; particularly, this longitudinal cohort study suggested a negative association between frequent tooth brushing and BMI.…”
Section: Discussionmentioning
confidence: 99%